1978
DOI: 10.1159/000169875
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Performance in Patients with Anorexia nervosa

Abstract: The heart function in 15 female patients with anorexia nervosa was examined by means of systolic time intervals. In 3 patients, pulmonary wedge pressure and cardiac output were measured. The findings indicate impaired myocardial contractility in patients with anorexia nervosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…42 Nudel et al 43 found abnormal cardiovascular and sympathetic responses to experimental physical exercise in adolescent girls with AN, and QT prolongation has also been reported in adults with AN. 9,10,19 Decreased myocardial contractility and impaired left ventricular function have been reported in adult women with AN, 11,15 but no differences were found in myocardial contractility in adolescent girls with AN compared with control subjects. 44 However, because cardiovascular events, especially arrhythmias, are a common cause of death in AN, 45 the high prevalence of bradycardia that we found in outpatient adolescent girls who have this eating disorder, although lower than in the 1988 study by Palla and Litt, 19 is disturbing.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…42 Nudel et al 43 found abnormal cardiovascular and sympathetic responses to experimental physical exercise in adolescent girls with AN, and QT prolongation has also been reported in adults with AN. 9,10,19 Decreased myocardial contractility and impaired left ventricular function have been reported in adult women with AN, 11,15 but no differences were found in myocardial contractility in adolescent girls with AN compared with control subjects. 44 However, because cardiovascular events, especially arrhythmias, are a common cause of death in AN, 45 the high prevalence of bradycardia that we found in outpatient adolescent girls who have this eating disorder, although lower than in the 1988 study by Palla and Litt, 19 is disturbing.…”
Section: Discussionmentioning
confidence: 98%
“…5,7 In addition to these serious complications of AN contributing to the mortality associated with this disorder, other significant changes have been reported in hemodynamic, hematologic, and bone metabolism parameters in adults with AN. [8][9][10][11][12][13][14] Although not life-threatening, these complications can be disabling and contribute to the morbidity of this disorder. Many of these complications result from physiologic adaptation to self-imposed starvation and malnourishment, and a large number are reversible with refeeding, at least in adults.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in cardiac mass and chamber dimensions present early in anorexia nervosa 15 and have been well studied. Consistently, decreases in left ventricular mass [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and left ventricular end-diastolic and left ventricular end-systolic dimensions 20,23,25,[29][30][31][32][33][34][35] are found; however, some controversy remains regarding some other very specific dimension measures, with some authors finding changes in left ventricular wall thickness [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] or left ventricular posterior wall thickness 2...…”
Section: Structural and Functional Cardiac Alterationsmentioning
confidence: 92%
“…For example, patients with anorexia nervosa (AN) are typically bradycardic (resting heart rate (HR) less than 50 per minute) and have relatively low arterial blood pressure (usually lower than 100/50 mm Hg) (Casper, 1986;Kalager, Brubakk, & Bassoe, 1978). Among others, cardiovascular abnormalities reported include QT-interval prolongation (Lesinskiene, Barkus, Ranceva, & Dembinskas, 2008;Takimoto et al, 2004), voltage decrease, T-wave inversion, weight reduction and thinning of the left ventricle, and drop of heart functional parameters (ejection fraction, minute blood volume) (Casiero & Frishman, 2006;Olivares et al, 2005).…”
Section: Introductionmentioning
confidence: 99%